COMPARATIVE STUDY OF LIFE SATISFACTION OF TEACHERS WORKING IN SUBSIDIZED AND PRIVATE B.ED. INSTITUTIONS - Panwar, Shubham; Singh, Bindu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Life satisfaction of teachers is not only related to their personal well-being, but it also has a profound impact on their professional efficiency, teaching quality and overall development of learners. The aim of the present research study is to do a comparative analysis of the level of life satisfaction of teachers working in subsidized (government aided) and private (private) B.Ed. institutions. This study makes it clear that the major factors affecting the life satisfaction of teachers are salary, job security, work environment, social recognition, work-life balance, and career progression prospects. Teachers working in subsidized B.Ed. institutions get the benefit of relatively more stability, regular salary, social security schemes, and better service conditions. In contrast, teachers working in private institutions often face low salaries, uncertain contracts, high workload, and low social recognition. Due to these reasons, teachers in aided institutions appear to be more satisfied with their lives, while teachers in private institutions are more stressed, insecure, and dissatisfied. The study also found that availability of physical resources, transparency of institutional administration, supportive environment, and leadership style are also determinants of teacher satisfaction. In institutions where the administration is collaborative, communicative, and democratic, the level of teacher satisfaction is relatively higher. Apart from this, family responsibilities, social relationships, mental health, and personal aspirations also affect life satisfaction. These factors are relatively more present in aided institutions, due to which teachers there appear to be more satisfied. In contrast, teachers working in private institutions feel anxious and insecure about their profession, which affects their life satisfaction.